El juego y la motricidad gruesa en los niños de 4 a 5 años del centro de educación inicial estancia Pekes ubicado en la ciudad de loja, en el período 2019 – 2020. - Encarnación Peñaloza, María Elena (2021)
The following investigation paper its titled: THE GAME AND THE GROSS MOTOR SKILLS IN 4–TO-5-YEAR-OLD CHILDREN OF THE INITIAL CENTER PEKES STAY LOCATED IN THE CITY OF LOJA, IN THE 2019 – 2020 PERIOD; it had, as a general objective, to analyze the importance of games in the gross motor skills in 4–to-5-year-old children. It was developed with a sample of 11 children and 1 teacher, the investigation type was a non-experimental with a mixed approach; in the thesis, a few methods were used to gather and analyze the information, the methods that were used were descriptive, analytical-synthetical and inductive – deductive. The directed interview to the initial II teacher was used as a technique and, as a diagnose instrument, the Development Abbreviated Scale (EAD-1) by Nelson Ortiz was used to know the problem´s prevalence in this children´s area, showing that most part of the surveyed population, corresponding to 73%, presents gross motor skills problems; for this reason, a game proposal entitled “Let's travel to the galaxy of games” was designed, these were oriented to strengthen the children´s gross motor skills in order to be applied when needed